PENGARUH BRAND ATTACHMENT, BRAND EXPERIENCE, & BRAND LOVE, TERHADAP BRAND EQUITY STUDY MEREK SCARLETT KOSMETIK - Trisno Trisno; Sri Yuliaty; Nurliya Apriyana (Jurnal Bina Bangsa Ekonomika, 2024)
The study has examined the influence of Brand Attachment, Brand Experience, and Brand Love on the Brand Equity focusing on cosmetic Scarlett brand. This research method is quantitative. This research collected primary data by online questionnaire of 100 respondents were knew about Scarlett whitening products. Data retrieval technique using google form questionnaire data. The sampling technique uses purposive sampling method. To prove empirically and validate the proposed model it tested by multiple linear regression methods with the help of SPSS program. The results showed that Brand Attachment, Brand Experience and Brand Love have a positive significant to the Brand Equity of Scarlett Whitening products. The importance of research in the beauty and skin care industry is expected to be a reference in the business world of management that can be used to optimize the development of product variations and brand utilization